Factors influencing the frequency of children's consumption of soft drinks - Pettigrew, Simone; Jongenelis, Michelle; Chapman, K.; Miller, C. (Academic Press, 2015)
Among other focus areas, interventions designed to improve children's diets need to address key factors contributing to children's consumption of sugar-sweetened beverages. The present study employed structural equation modelling to investigate the relationship between a broad range of predictor variables and the frequency with which Australian children consume soft drinks. In total, 1302 parents of children aged 8 to 14 years responded to an online survey about their children's food consumption behaviours. Soft drink consumption frequency was primarily influenced by parents' attitudes to soft drinks, children's pestering behaviours, and perceived social norms relating to children's consumption of these products. Importantly, pestering and social norms had significant direct effects on consumption frequency in addition to indirect effects via their impact on parents' attitudes to soft drink.